2002
DOI: 10.1177/1357633x0200800302
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing for Continuing Medical Education: From Pilot Project to Sustained Programme

Abstract: Videoconferencing has been used to provide distance education for medical students, physicians and other health-care professionals, such as nurses, physiotherapists and pharmacists. The Dalhousie University Office of Continuing Medical Education (CME) has used videoconferencing for CME since a pilot project with four sites in 1995-6. Since that pilot project, videoconferencing activity has steadily increased; in the year 1999-2000, a total of 64 videoconferences were provided for 1059 learners in 37 sites. Vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…As a result, video conferences tended to be costly. 5 At present, having a personal computer and Internet access is almost the norm for physicians, which makes it possible for almost anyone to participate in the webinars easily with no added cost regardless of their location, even in very remote areas. It has also become easy to develop and maintain an online archive of the past handouts of webinars that are accessible to participants at any time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, video conferences tended to be costly. 5 At present, having a personal computer and Internet access is almost the norm for physicians, which makes it possible for almost anyone to participate in the webinars easily with no added cost regardless of their location, even in very remote areas. It has also become easy to develop and maintain an online archive of the past handouts of webinars that are accessible to participants at any time.…”
Section: Discussionmentioning
confidence: 99%
“…23 Interaction during videoconferences or webinars has been known to occur via voice and/or by text chats. 5 , 24 In CPD videoconferences or webinars intended primarily for physicians, vocal interaction among learners has been reported, but no study has thus far reported on an extensive use of chat tools or their effect or usefulness in interaction. 25 There is also a lack of research on how webinars for primary care physicians are conducted over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha visto que el apoyo de la facultad y el buen estado de los equipos es fundamental en este proceso de aprendizaje (24).…”
Section: Resultsunclassified
“…Parece ser que los componentes importantes en una videoconferencia en línea incluyen: planeación, apoyo que la facultad o escuela brinde para el desarrollo, apoyo técnico que incluye audio y video adecuados, mantenimiento de los equipos y evaluación del programa (24). Para los estudiantes, los retos de este método se relacionan con la motivación y participación en clase, así como sus estilos de aprendizaje (25).…”
Section: Introductionunclassified
“… 24 Videoconferencing is frequently used in graduate and continuing medical education. 25 , 26 The AAMC has recently introduced a resource guide for standardized video interview operational pilot, discussing how to register, interview policies, rules to protect interview integrity, and post-interview procedures. 27…”
Section: Discussionmentioning
confidence: 99%